Kucecwara Chic, Ragam Fungsi Untuk Malang Dalam Batikku Siswiyani - Syarafina, Nanda; Nurhadi, Nurhadi; Riska, Yuliana; Cynthia, Persijn Ayura; Dyah, Ratnasari Siwi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Batik Unfortunate yet widely known both nationally and internationally. Batik Malangan able to penetrate world markets, in particular the intended market share are the young people and the general public. The idea was to create a bag that can be personalised way it functions with a touch of Malangan batik motifs with the name